2017
DOI: 10.4314/jasem.v21i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malaria and geohelminth co-infection among antenatal women at the Federal Medical Centre and Specialist Hospital, Yola, Adamawa Sate, Nigeria

Abstract: Malaria and geohelminths are known to be associated with pregnancy within all age groups. The objective of this study was to determine the prevalence of malaria and geohelminths co-infection among pregnant women. The study was conducted on 252 pregnant women who came for antenatal visits at Federal Medical Center and Specialist Hospital within Yola metropolis from July to November 2015. Socio-demographic information of the pregnant women was collected. Capillary blood from finger prick was used for malaria scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Contrary findings have been reported in a study in Nigeria in which no cases of still birth and low birth weight were recorded among pregnant mothers coinfected with malaria and geohelminths [22]. It is not clear whether the study subjects were allowed access to antimalarials, anthelmintics, or hematinics before or during the study.…”
Section: Discussionmentioning
confidence: 59%
“…Contrary findings have been reported in a study in Nigeria in which no cases of still birth and low birth weight were recorded among pregnant mothers coinfected with malaria and geohelminths [22]. It is not clear whether the study subjects were allowed access to antimalarials, anthelmintics, or hematinics before or during the study.…”
Section: Discussionmentioning
confidence: 59%
“…Ten studies were reported from Nigeria [96][97][98][99][100][101][102][103][104][105][106], and three studies were from Kenya [69,107,108] and Uganda [109][110][111]. Two studies were reported from Ethiopia [112,113], Gabon [114,115], and Ghana [116,117], respectively. The remaining studies were reported from Malawi [118] and Cameroon [119].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%